Region, innovation and knowledge in strategy of European Union economic growth and social security - Puślecki, Zdzisław W. (Rocznik Integracji Europejskiej, 2015)
The main aim of this paper is an analysis of the region in general form and to look at innova- tion and knowledge in the European Union’s economic growth and social security strategy. The research objectives here encompass the presentation of the innovation system and knowledge in promoting entrepreneurship, the theoretical concept of the innovation system and process at the level of the region, the knowledge-based economy, constructed advantage, the constructed advantage provided by the Triple Helix model, Europe 2020 strategy, Innovation Union and Horizon 2020 as the financial instruments implemented by the Innovation Union. An important result of the research is the conclusion that in the innovation process the connections between science (universities), market (industry) and government are very important. There is a positive dependence between innovation activities and the effectiveness of the innovation process. More interaction and cooperation can be observed on the regional than on the state level. The new programmes of scientific and innovation research, Europe 2020 and the Innovation Union, are very important factors in the strategy of the European Union’s economic growth and social security.